1999
DOI: 10.1136/qshc.8.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Influences on clinical practice: the case of glue ear

Abstract: A case study of clinical practice in children with glue ear is presented. The case is part of a larger project, funded by the North Thames Research and Development Programme, that sought to explore the part played by clinicians in the implementation of research and development into practice in two areas: adult asthma and glue ear in children.What is striking about this case is the diVerences found in every area of the analysis. That is, diversity was found in views about diagnosis and treatment of glue ear; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Other studies have already shown that it is difficult to trace the factors involved in dissemination and applicability of trial results [10,11]. Our results show that the Bayesian approach appears to be a paradigm, i.e.…”
Section: Discussionmentioning
confidence: 37%
“…Other studies have already shown that it is difficult to trace the factors involved in dissemination and applicability of trial results [10,11]. Our results show that the Bayesian approach appears to be a paradigm, i.e.…”
Section: Discussionmentioning
confidence: 37%
“…Organizational context and current clinical practice are influenced by history, that is to say people work within an inherited set of organization and policy arrangements that set an important part of the context for treatment. Clinicians rarely acknowledge that the organization and management of services are important influences on clinical practice yet time and again they appear as important if unacknowledged influences (Dopson, Miller, Dawson, & Sutherland, 1999). Sustained political and managerial support and pressure for clearly defined change at a local level.…”
Section: Policy and Managerial Implicationsmentioning
confidence: 99%
“…Building on this foundation, early results from research in the healthcare sector in the UK (Fairhurst & Huby 1998, Dopson et al . 1999, Fitzgerald et al .…”
Section: Introductionmentioning
confidence: 99%